Influence of New Zealand cockles (Austrovenus stutchburyi) on primary productivity in sandflat-seagrass (Zostera muelleri) ecotones. (5th November 2016) - Lohrer, Andrew M.; Townsend, Michael; Hailes, Sarah F.; Rodil, Iván F.; Cartner, Katie; Pratt, Daniel R.; Hewitt, Judi E.
Abstract: New Zealand cockles ( Austrovenus stutchburyi ) are ecologically important, intertidal bivalves that have been shown to influence nutrient cycles and the productivity of microphytobenthos on sandflats. Here, we investigated the potential for cockles to impact the productivity of seagrass, Zostera muelleri, and examined interactions between these habitat-defining species where they co-occur. We sampled bivalve densities and sizes, sediment properties, and seagrass shoot densities across the boundaries of two seagrass patches on an intertidal sandflat in northern New Zealand, and measured dissolved oxygen and nutrient fluxes in light and dark benthic incubation chambers in conjunction with a 0–97% gradient in seagrass cover. Although gross primary production (GPP, μmol O2 m −2 h −1 ) increased predictably with the cover of live seagrass, the density of cockles and sediment properties also contributed directly and indirectly. Seagrass cover was positively correlated with cockle density (ranging from 225 to 1350 individuals per m 2 ), sediment mud percentage (0.5–9.5%), and organic matter content (0.5–2.2%), all of which can affect the efflux of ammonium (readily utilisable inorganic nitrogen) from sediments. Moreover, the cover of green seagrass blades plateaued (never exceeded 70%) in the areas of highest total seagrass cover, adding complexity to cockle-seagrass interactions and contributing to a unimodal cockle-GPP relationship. Graphical abstract: Highlights: Various habitat types occur as a patchwork on intertidal flats in New Zealand. Transitions between cockle beds and seagrass meadows contain both species. Transitional gradients in sediment properties and fauna affect nutrient dynamics. Cockles have an indirect positive effect on seagrass primary productivity. Cockles bioturbate sediment and impact productivity most at intermediate densities.